A Study on the Willingness of State Islamic Religious Council to Support Waqf Development in Higher Education - Fadhilah Abdullah Asuhaimi; Mohammad Haji Alias; Zurina Shafii; Nursilah Ahmad (Universiti Sains Islam Malaysia, 2024)
In Malaysia waqf is regulated and managed by the State Islamic religious council (SIRC) in each of the states. This requirement is also applied to the higher education institutions. However, not all the SIRCs are willing to grant the mutawalli status to the higher education institutions due to the certain reasons. This paper investigates the willingness of selected SIRCs in granting the mutawalli status to the higher education institutions. In this study, respondents from six SIRCs which have involvement with higher education institutions were interviewed. The six SIRCs are from the states of Johor, Negeri Sembilan, Selangor, Perak, Penang and the Federal Territories of Kuala Lumpur. The findings were analysed using the interpretative analysis. It was found that one SIRC is not willing to grant the mutawalli status viz. Federal Territories of Kuala Lumpur Islamic Religious Council. In the states in which waqf is not enacted, it is suggested that the SIRCs could consider putting a provision to grant the mutawalli status to those who are competent.